185k views
1 vote
Please please help show all work

Please please help show all work-example-1

1 Answer

4 votes

to find the inverse of any expression, we start off by doing a quick switcheroo on the variables, and then solve for the dependent variable, usually y.



image


3)


now, we do the same for G(x), to get its inverse



\bf \stackrel{G(x)}{y}=\cfrac{x+3}{2}\implies \stackrel{\textit{quick switcheroo}}{\underline{x}=\cfrac{\underline{y}+3}{2}}\implies 2x=y+3\implies 2x-3=y\impliedby F(x)

User BadFileMagic
by
5.5k points